Operations research methods - Bose, Sujit K. (ALpha Science, 2005)
The book consists of eight chapters as detailed in the contnets. The short opening chapter describes the nature of operations research prob-lems in generals terms. The second chapter on linear Programming (there is increasing evidence in mathematical circles to prefer the term"opti-misation" instead of the historic " programming" is lengthy in view of the issues involved. The remaining five chapters on transportation and Assignment, Networks, Integer and Dynamic programming